Osteosynthesis versus endoprosthesis for the treatment of femoral neck fracture in Asian elderly patients. Issue 1 (December 2016) - Kang, Joon; Jeon, Yoon; Ahn, Chi; Roh, Tae
Abstract Background The purpose of this study was to compare the clinical results between osteosynthesis and endoprosthesis for femoral neck fractures in asian elderly patients, and to analysis the factors that may affect the failure of osteosynthesis. Methods A retrospective review of 382 hips over 65-year old with femoral neck fracture was done. Within non-displaced fracture group, 81 cases (56.6 %) underwent internal fixation (IF) and with 62 cases (43.3 %) having bipolar hemiarthroplasty (BPHA). As for displaced fracture group, 60 cases (25.1 %) underwent internal fixation (IF) with 179 cases (74.8 %) having BPHA. Average follow-up period for the patients was 36.8 months. Analysis was conducted on complications depending on fracture types and osteoporosis, and clinical evaluation was done on gait capability by using Koval walking ability. Results In non-displaced group, BPHA group showed statistically significant lower percentage of complications compared to IF group, but re-operation rate and the degradations of Koval score were no significant differences. In displaced group, complication, re-operation rate and the degradations of Koval score of BPHA group were statistically better than those of IF group. Association between osteoporosis and non-union is no statistically significant. Conclusions Endoprosthetic replacement could be a primary option for displaced femoral neck fracture in elderly asian patients. The choice of surgical treatment methods of non-displaced fracture in elderly asian patients should be determined carefully considering the age and the presence of osteoporosis.